Community-Based Fishery Management In The Post Conflict Situation: A Case Study In Coastal Villages, North Maluku, Indonesia - Sidayat, Mardiyani (Journal of Rural Indonesia [JORI], 2014)
The paper uses a case-study of the coastal villages in North Maluku, Indonesia that is in the process of reconciliation between the Muslim and Christian. The paper attempts to contribute to the understanding of the use of traditional Community Based Fishery Management (CBFM) in facilitating the reconciliation process in the post-violent conflict. The paper begins by examining catalyzed factors contributing to the use of CBFM in the post violent conflict period. Subsequently, the paper continues by exploring the outcomes of CBFM and its affect in rebuilding relationships. The paper ends with briefly analyses to the sources of tension which perhaps come out from a control over fishery resources and unequal power relations between the Muslims and the Christians. This study found that it is possible for CBFM to facilitate the reconciliation with respect to two factors. Firstly, shared rules and cultural values promote cooperative behavior and enhance solidarity. And secondly, the role of the community leader as a mediator of community conflict allows disputes to be settled in relatively fair and amicable manner. It is hoped that a lesson from this study can be applied to provide an understanding of the traditional community-based management and its dynamic role in helping to facilitate the reconciliation. Â© 2014 Journal of Rural Indonesia [JoRI] IPB. All rights reserved. Keywords: community, fishery, management, conflict